2017
DOI: 10.1371/journal.pone.0172827
|View full text |Cite
|
Sign up to set email alerts
|

Tablet computer enhanced training improves internal medicine exam performance

Abstract: BackgroundTraditional teaching concepts in medical education do not take full advantage of current information technology. We aimed to objectively determine the impact of Tablet PC enhanced training on learning experience and MKSAP® (medical knowledge self-assessment program) exam performance.MethodsIn this single center, prospective, controlled study final year medical students and medical residents doing an inpatient service rotation were alternatingly assigned to either the active test (Tablet PC with custo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 29 publications
0
24
0
1
Order By: Relevance
“…Several previous studies have evaluated mobile technology's influence on educational outcomes. 16,[20][21][22][23] In a study by Moodley et al, infectious disease fellows identified 24 iPad applications to facilitate their clinical tasks, decision-making, and education. 24 In neurosurgical training, easily accessible information and portability guaranteed by tablets provided more opportunities and time for 92% of residents polled, and was associated with improved performance on 16 of 18 domains on the Congress of Neurological Surgeons Self-Assessment Examination.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have evaluated mobile technology's influence on educational outcomes. 16,[20][21][22][23] In a study by Moodley et al, infectious disease fellows identified 24 iPad applications to facilitate their clinical tasks, decision-making, and education. 24 In neurosurgical training, easily accessible information and portability guaranteed by tablets provided more opportunities and time for 92% of residents polled, and was associated with improved performance on 16 of 18 domains on the Congress of Neurological Surgeons Self-Assessment Examination.…”
Section: Discussionmentioning
confidence: 99%
“…At least Wilhelm von Humboldt believed in it, creating the model of university in its present form at the beginning of the nineteenth century. digital educational materials [11] are being created for the fi rst time; the content of higher education is being updated in the context of global trends [12]. "The new large data can be used for deeper assessment of knowledge and skills, deepening the links between all levels of learning, establishing contacts between educational institutions, students and employers, rating academic progress" 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Thus, they suggested electronic instruction at rst followed by holding several classes for in-person problem solving. A recent study reported enhanced medical education and exam performance following tablet computer-based integrated training and clinical practice [46].…”
Section: Discussionmentioning
confidence: 99%